2023
DOI: 10.1108/sef-04-2023-0187
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bitcoin on gold, the volatility index (VIX), and dollar index (USDX): analysis based on VAR, SVAR, and wavelet coherence

Abstract: Purpose Since 2008, bitcoin has continued to attract investors due to its growing capitalization and opportunity for speculation. The purpose of this paper is to analyze the impact of bitcoin (BTC) on gold, the volatility index (VIX) and the dollar index (USDX). Design/methodology/approach The series used are weekly and cover the period from January 2016 to November 2022. To generate the results, the unrestricted vector autoregression (VAR), structural vector autoregression (SVAR) and wavelet coherence were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Ibrahim and Ali Basah (2022) found that there is no Granger causality between gold and Bitcoin. Moreover, scholars have also focused on the spillover effect between Bitcoin and gold (Yu et al 2021;Aliu et al 2023), dynamic linear correlations (Kang et al 2019;Jin et al 2019;Klein et al 2018), and nonlinear correlations (Jareño et al 2020;Zwick and Syed 2019;Kim et al 2020;Kumar et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Ibrahim and Ali Basah (2022) found that there is no Granger causality between gold and Bitcoin. Moreover, scholars have also focused on the spillover effect between Bitcoin and gold (Yu et al 2021;Aliu et al 2023), dynamic linear correlations (Kang et al 2019;Jin et al 2019;Klein et al 2018), and nonlinear correlations (Jareño et al 2020;Zwick and Syed 2019;Kim et al 2020;Kumar et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As widely acknowledged by previous studies [1,2], Bitcoin presents a highly volatile investment opportunity, but this volatility also offers substantial speculative potential. As the pandemic unfolded, numerous investigations explored Bitcoin's role, analyzing its relationship with traditional financial markets [3][4][5] and its impact on market efficiency [6].…”
Section: Introductionmentioning
confidence: 99%